Assessing the Presence of IgG Antibodies against Influenza Viruses in Neonates after Maternal Vaccination and Factors That May Affect the Transplacental Transfer - Chrysoula Taskou; Antigoni Sarantaki; Vasiliki Ε. Georgakopoulou; Gerasimos A. Spyratos; Panagiotis V. Drossos; Georgios Daskalakis; Apostolos Beloukas; Aikaterini Lykeridou (Diseases, 2023)
Special populations, particularly pregnant women, are uniquely susceptible to infectious diseases due to alterations in their immunological, respiratory, and cardiovascular systems during gestation. Influenza infections during the perinatal period have been associated with more severe maternal and perinatal outcomes, underscoring the critical importance of vaccination data for pregnant women. According to the World Health Organization (WHO), all pregnant women and those of childbearing age should receive the inactivated influenza vaccine, irrespective of their pregnancy stage. This study aimed to elucidate factors influencing neonatal antibody presence following maternal influenza vaccination. Conducted through convenience sampling in Athens, Greece, this study involved 78 pregnant women who received flu vaccinations. The participants completed questionnaires covering demographics, obstetric history, attitudes toward influenza vaccination, and knowledge about the influenza virus and pregnancy vaccination. Blood samples were collected from 83 neonates to assess IgG antibody presence. Five of the surveyed women had twin pregnancies. The statistical analysis employed IBM SPSS-Statistics version 26.0. This study revealed the presence of positive influenza A and B antibodies in neonates following maternal immunization. Furthermore, it identified factors such as the gestational week and timing of vaccination during pregnancy that influenced the transfer of antibodies from mother to fetus. These findings offer valuable insights for healthcare professionals to provide informed recommendations on influenza vaccination during pregnancy and empower expectant mothers to make informed decisions about the benefits of immunization.